A practical model of the diffusion of oil‐based fluid into polyethylene. Issue 11 (13th October 2020) - Zaribaf, Fedra P.; Hassuji, Tahir A.; Cookson, Andrew N.; Gill, Harinderjit S.; Pegg, Elise C.
Abstract: It is possible to modify the properties of semicrystalline polymers using diffusion to introduce additional functionality. For example, Vitamin E infused polyethylene has antioxidant properties, which enhances the longevity of the polyethylene. Lipiodol ultra fluid, an iodinated oil‐based contrast agent, can be used to enhance the X‐ray attenuation of medical grade polyethylene. To manufacture a part geometry with a sufficiently even distribution of oil for radiopacity, while maintaining the thermally dependent properties of the polymer (e.g., crystallinity) is a challenge. Rather than relying on trial and error, this study aimed to identify the simplest, most practical model, which could assist with planning for manufacturing of such parts. Models in 1D, 2D, and 3D were examined but only the 3D Fickian model was able to predict the profile of oil diffusion within polyethylene with suitable performance (as low as 7% inaccuracy for some diffusion conditions). The model was more accurate at the surface of the samples and at lower diffusion temperatures. The 3D Fickian model used in this study was capable of estimating the oil concentration in the surface of a polyethylene part after diffusion to a sufficient accuracy for planning manufacturing processes of oil‐infused polyethylene parts. Abstract :